(untitled) (Proceedings of International Conference on Special Education, 2025)
Multiplication remains a significant challenge for remedial students, particularly in understanding and applying its concepts due to complex representations that hinder comprehension. Furthermore, parents often expressed being unable to teach the concept at home. To address these challenges, the KOKALI technique—an acronym for "ko" (kotak, meaning box), "ka" (kali, meaning times), and "li" (lidi, meaning sticks)—was developed to simplify multiplication using simple and consistent representations. This innovative approach aims to facilitate learning comprehension and parents’ involvement in teaching multiplication concept by utilizing boxes and sticks to represent multiplication factors. This classroom action research explores the efficacy of the KOKALI technique in enhancing students’ understanding. Data were collected from classroom observations, diagnostics test and post-tests using single-blind testing methods among 20 remedial students (aged 8–9) at SK Membedai, WP Labuan, over 12 sessions. Feedback from 25 parents was gathered via a digital survey during a KOKALI workshop to assess the technique’s effectiveness. Results indicated a significant improvement, with over 90% of students successfully solving single-digit by two-digit and three-digit multiplication sentences without regrouping using the KOKALI technique. Classroom observations revealed that students displayed increased confidence in their mathematical abilities, as they were able to complete multiplication tables from 1 to 9 using KOKALI. Additionally, over 90% of parents surveyed strongly agreed that KOKALI is highly beneficial in helping children understand multiplication, as its simplicity makes it easy to apply and explain at home. The findings show that the KOKALI technique is useful not only for remedial students but also for early mathematics education. By incorporating this approach, educators can overcome barriers to mastering multiplication and emphasize the need for innovative teaching methods to support students’ mathematical development.